2021
DOI: 10.1021/acsabm.1c00225
|View full text |Cite
|
Sign up to set email alerts
|

Gentamicin-Releasing Titania Nanotube Surfaces Inhibit Bacteria and Support Adipose-Derived Stem Cell Growth in Cocultures

Abstract: Infection is the second leading cause of failure of orthopedic implants following incomplete osseointegration. Materials that increase the antimicrobial properties of surfaces while maintaining the ability for bone cells to attach and proliferate could reduce the failure rates of orthopedic implants. In this study, titania nanotubes (Nts) were modified with chitosan/heparin polyelectrolyte multilayers (PEMs) for gentamicin delivery. The antimicrobial activity of the surfaces was tested by coculturing bacteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Topical gentamicin has several advantages: it does not damage renal function and has a low risk of drug-resistant pathogens, it kills bacteria by inhibiting protein synthesis, and it destroys the stability of the bacterial bilayer membrane 24 . Wigmosta et al 42 discovered that delivering gentamicin from the surface is superior to delivering gentamicin in a solution, which could improve the antimicrobial activity of orthopedic implants and lower the risk of infection-induced failure without reducing mammalian cell attachment. Further, gentamicin and curcumin-loaded lipid-polymer hybrid nanoparticles have excellent antibacterial properties and are promising antibacterial agents for the treatment of chronic infections and intracellular bacteria 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Topical gentamicin has several advantages: it does not damage renal function and has a low risk of drug-resistant pathogens, it kills bacteria by inhibiting protein synthesis, and it destroys the stability of the bacterial bilayer membrane 24 . Wigmosta et al 42 discovered that delivering gentamicin from the surface is superior to delivering gentamicin in a solution, which could improve the antimicrobial activity of orthopedic implants and lower the risk of infection-induced failure without reducing mammalian cell attachment. Further, gentamicin and curcumin-loaded lipid-polymer hybrid nanoparticles have excellent antibacterial properties and are promising antibacterial agents for the treatment of chronic infections and intracellular bacteria 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Drug delivery coating systems can provide direct delivery of pharmaceuticals at the targeted bone‐implant interface. In particular, polymeric matrix‐based drug delivery coating systems have been designed to provide solutions for implant related infections (Inzana et al., 2016; Pan et al., 2018), osteomyelitis treatments and also for the inhibition of bacterial biofilm formation on the implant surface (Wigmosta et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Long term, high‐dose Gm therapy has been associated with bacterial antibiotic resistance (Ben‐Nissan et al., 2013; Ribeiro et al., 2012). Additionally, it has been reported that various antibiotics including gentamycin, rifampicin, penicillin, and streptomycin cause dose‐dependent negative effects on the biological properties and regenerative potential of human ADSCs including growth, proliferation, and differentiation (Rady et al., 2020; Skubis et al., 2017; Wigmosta et al., 2021). To avoid negative effects on ADSC, the antibiotics should be applied at adequate concentration for a sufficient time (Lotfi et al., 2020).…”
Section: Introductionmentioning
confidence: 99%